1983
DOI: 10.1128/aac.23.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant septal peptidoglycan synthesis in a methicillin-resistant Staphylococcus aureus strain

Abstract: In a methicillin-resistant Staphylococcus aureus strain, electron micrographs showed that cell wall septa continued to be formed in the presence of methicillin, although they became distorted and enlarged. The results indicated that peripheral cell wall synthesis was inhibited. It is concluded that a methicillin-resistant mode of septal peptidoglycan synthesis is an important determinant of methicillin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…The response of peptidoglycan synthesis to methicillin in chloramphenicol-inhibited cultures, in which no induction of PBP 2' production by the challenging methicillin can occur (5), showed the same pattern. However, the peptidoglycan synthesis occurring in chloramphenicol-inhibited cultures is believed to represent wall thickening rather than septal peptidoglycan synthesis (24,29). Nevertheless, these results provide supporting evidence for the supposition that PBP 2' represents a ,-lactam-insensitive peptidoglycan transpeptidase which al- At 30°C, growth with NaCl clearly increased PBP 2' production but peptidoglycan synthesis was no more methicillin resistant.…”
Section: Resultscontrasting
confidence: 39%
See 3 more Smart Citations
“…The response of peptidoglycan synthesis to methicillin in chloramphenicol-inhibited cultures, in which no induction of PBP 2' production by the challenging methicillin can occur (5), showed the same pattern. However, the peptidoglycan synthesis occurring in chloramphenicol-inhibited cultures is believed to represent wall thickening rather than septal peptidoglycan synthesis (24,29). Nevertheless, these results provide supporting evidence for the supposition that PBP 2' represents a ,-lactam-insensitive peptidoglycan transpeptidase which al- At 30°C, growth with NaCl clearly increased PBP 2' production but peptidoglycan synthesis was no more methicillin resistant.…”
Section: Resultscontrasting
confidence: 39%
“…However, such cells were not growing normaily. Their peptidoglycan was poorly cross-linked (18,31), their septa were enlarged, and their division was aberrant (29). Perhaps growth eventually stops because the normal synthesis and maturation of peptidoglycan is interfered with, even though PBP 2' may be capable of synthesizing more peptidoglycan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electron micrographic studies of a methicillin-resistant strain grown in methicillin revealed thickened septa, attributed to unbalanced growth and diversion of cell wall material into the septum at the expense of the peripheral, nonseptal wall (171 (114,157). The National Committee for Clinical Laboratory Standards currently recommends the use of 2% NaCl, an inoculum of 5 x 105 CFU/ml, and incubation for 24 h at a temperature of 350C.…”
Section: Other Factorsmentioning
confidence: 99%